Relationship between visual span and reading performance in Age-Related Macular Degeneration - Cheong, Allen MY (2008)
PURPOSE: Visual-span profiles are plots of letter-recognition accuracy as a function of letter position left and right of the point of fixation. Legge, Mansfield & Chung (2001) proposed that reduced size of the visual span is a spatial factor limiting reading speed in patients with age-related macular degeneration (AMD). We have recently shown that a temporal property of letter recognition - the exposure time required for a high level of accuracy – is also a factor limiting reading speed in AMD (Cheong, Legge, Lawrence, Cheung & Ruff, 2007). We measured the visual-span profiles of AMD subjects and assessed the relationship of the spatial and temporal properties of these profiles to reading speed. METHODS: Thirteen AMD subjects and 11 age-matched normals were tested. Visual-span profiles were measured by using the trigram letter-recognition method described by Legge et al. (2001). Each individual’s temporal threshold for letter recognition (80% accuracy criterion) was used as the exposure time for measuring the visual-span profile. Size of the visual span was computed as the area under the profile in bits of information transmitted. The information transfer rate in bits per second was defined as the visual-span size in bits divided by the exposure time in sec. RESULTS: AMD visual-span sizes were substantially smaller (median of 23.9 bits) than normal visual-span sizes in central vision (median of 40.8 bits, p<0.01). For the nine AMD subjects with eccentric fixation, the visual-span sizes (median of 20.6 bits) were also significantly smaller than visual spans of normal controls at 10° below fixation in peripheral vision (median of 29.0 bits, p=0.01). Information transfer rate for the AMD subjects (median of 29.5 bits/sec) was significantly slower than that for the age-matched normals at both central and peripheral vision (median of 411.7 & 290.5 bits/sec respectively, ps<0.01). Information transfer rates were more strongly correlated with reading speed than the size of the visual span, and explained 36% of the variance in AMD reading speed. CONCLUSION: Both visual-span size and information transfer rate were significantly impaired in the AMD subjects compared with age-matched normals. Information transfer rate, representing the combined effects of a reduced visual span and slower temporal processing of letters, was a better predictor of reading speed in AMD subjects than was the size of the visual span.